PROSPEK PENGEMBANGAN AGROINDUSTRI OLAHAN JAGUNG DI KABUPATEN KUPANG - Krisna Setiawan; Ferdy A.I. Fallo (Partner, 2010)
Development Prospects Agroindustry Processed Corn in Kupang Regency. This research was conducted in Kupang regency in March until October 2009. Samples of processed corn agro-industry players are determined by purposive sampling. Data analysis methods include: Financial Analysis, Value Added Analysis, Analysis and Development Strategy Prepared Agoindustri Corn. Results showed that processed corn Agroindustry financially beneficial to employers because: the mean acceptance of all three types of processed corn is greater than the average cost so that positive profits, the value of R/C of the three types of corn processing more than one and the amount of actual production and actual receipts have been exceed breakeven. There is the added value of every one kilogram of processed corn chips, amounting to Rp 5425 (0.82%), and Rp 27.500 (0.71%) to Marning corn and Lepa corn Rp 6.500,5 (0.37%). The strategy should be done in the development of refined corn agro-industry: increasing the number of production to meet market demand, improve the quality of processed food corn, so that it can compete with similar products on the market, increase capital and expand the marketing area through the promotion or through partnerships with parties who have wide market network as well as efficiency of production.Keywords: Agroindustry, processed food corn, financial analysis, value added, SWOT analysis